2015
DOI: 10.1515/pesd-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

The Physico-Mechanical Characteristics of the Clays in and After Doping With Metal Oxide Al2O3 in the Region of Fez (Morocco)

Abstract: Abstract. Miocene marl is one of the widespread geological substrates in Fez vicinity (Central Morocco). In this study we proceed by a physicochemical characterization of the marl after doping with metal oxides, by various analytical techniques, namely the X-ray fluorescence, the mineralogical analysis, and dielectric property. The doping of these marl was conducted by solid oxides of Al 2 O 3 at different percentages (5%, 10% and 15%). The results of chemical analysis showed the Al 2 O 3 increase during dopin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The observed change in chemical components of burned marl, pozzolan and cellulose mixtures might explain how high CaO contents may turn the marl color to yellowish and pinkish shades. The presence of CaO leads to a high mechanical strength in marl (Mesrar, al., 2015). Mullites and Metakaolinite often develop within the burning process of marl and make it more valuable for economic activities.…”
Section: Syntheses and Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…The observed change in chemical components of burned marl, pozzolan and cellulose mixtures might explain how high CaO contents may turn the marl color to yellowish and pinkish shades. The presence of CaO leads to a high mechanical strength in marl (Mesrar, al., 2015). Mullites and Metakaolinite often develop within the burning process of marl and make it more valuable for economic activities.…”
Section: Syntheses and Relevancementioning
confidence: 99%
“…The production of environmentally friendly materials and inexpensive used materials are of interest for craft and industry activities (ceramics, cooking pots, tiles, etc.). Several approaches have been reported in the literature concerning the use of certain industrial additives or wastes as cementing agents to improve the properties performance of clay and marl raw materials (Gidley and Sack 1984,), clay soils (Kolias et al, 2005, Yong and Ouhadi, 2007, Mesrar et al, 2015, residual soils (Miller and Azad, 2000), fly ash from rice husk , artificial pozzolan (Al-Rawas et al, 2005) and geopolymers (Akdim et al, 2017;Mesrar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A major problems encountered by users of these materials is their fragility and high shrinkage induced by cooking and causing defects in the bricks [6], and can go until it bursts. In order to improve the material performance, the efficiency and the quality in the manufacture of this marl, we opted for doping by dry method this material by the pozzolan, at different percentages of 5, 10, 15 and 20%.…”
Section: Introductionmentioning
confidence: 99%
“…Several brief studies have been conducted on these Fez clays, with their characterization differing from one study to another. For example, some studies state that the Fez clays are composed of illite, chlorite, kaolinite and smectite (El Ouahabi et al, 2014;Achiou et al, 2016), while other studies have reported that these clays are devoid of smectite and chlorite (Mesrar et al, 2012(Mesrar et al, , 2013.…”
mentioning
confidence: 99%